2007
DOI: 10.1177/0044118x08314233
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of the Model Minority Story

Abstract: The image of the model minority dominates scholarly and public discourse on Asian American children and adolescents. However, recent research has shown that despite their high levels of educational achievement Asian American students report poor psychological and social adjustment. Using an ecological framework, this article sought to explore the family and peer experiences of Chinese American adolescents as these are the two most critical contexts influencing adolescents' psychological and social adjustment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…During early adolescence, youth begin to develop a more nuanced awareness of negative ethnic and race‐related messages and interactions with adults and peers outside the family in the form of discrimination and unfair treatment (Brown & Bigler, 2005; Hughes & Johnson, 2001; Verkuyten & Kinket, 2000; Verkuyten, Kinket, & van der Weilen, 1997). Studies increasingly suggest deleterious consequences of ethnic and racial discrimination for psychological well‐being among early adolescents (Brody et al, 2006; Rivas‐Drake, Hughes, & Way, 2008; Romero & Roberts, 1998, 2003; Wong et al, 2003) as well as among older adolescents (Chavous, Rivas‐Drake, Smalls, Griffin, & Cogburn, 2008; Greene et al, 2006; Qin, Way, & Pandy, 2008; Sellers et al, 2006). Although few studies have examined relationships between discrimination experiences and adolescents' developing self‐beliefs and perceptions about ethnicity, those that exist typically find significant relationships (Pahl & Way, 2006; Romero & Roberts, 1998, 2003; Sellers & Shelton, 2003; Sellers et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…During early adolescence, youth begin to develop a more nuanced awareness of negative ethnic and race‐related messages and interactions with adults and peers outside the family in the form of discrimination and unfair treatment (Brown & Bigler, 2005; Hughes & Johnson, 2001; Verkuyten & Kinket, 2000; Verkuyten, Kinket, & van der Weilen, 1997). Studies increasingly suggest deleterious consequences of ethnic and racial discrimination for psychological well‐being among early adolescents (Brody et al, 2006; Rivas‐Drake, Hughes, & Way, 2008; Romero & Roberts, 1998, 2003; Wong et al, 2003) as well as among older adolescents (Chavous, Rivas‐Drake, Smalls, Griffin, & Cogburn, 2008; Greene et al, 2006; Qin, Way, & Pandy, 2008; Sellers et al, 2006). Although few studies have examined relationships between discrimination experiences and adolescents' developing self‐beliefs and perceptions about ethnicity, those that exist typically find significant relationships (Pahl & Way, 2006; Romero & Roberts, 1998, 2003; Sellers & Shelton, 2003; Sellers et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Discrimination based on ethnic group membership also occurs among peers, although studies that examine differences in adult and peer sources of ethnic discrimination have only recently emerged (e.g., Fisher et al, 2000; Greene et al, 2006; Hughes & Johnson, 2001; Pahl & Way, 2006; Rivas‐Drake et al, 2008; Rosenbloom & Way, 2004; Szalacha et al, 2003; Wong et al, 2003). Peer ethnic and racial discrimination manifests in multiple ways, including intentional or overt social exclusion, teasing, hitting, and unfair treatment based on ethnic group membership (Brown & Bigler, 2005; Chavous et al, 2008; Greene et al, 2006; Qin et al, 2008; Rosenbloom & Way, 2004; Verkuyten & Steenhuis, 2005; Wong et al, 2003). For example, 18% of Puerto Rican adolescents report discrimination by classmates (Szalacha et al, 2003) and 84% of East Asian and 73% of South Asian youth report being called racially derogatory names (Fisher et al, 2000).…”
mentioning
confidence: 99%
“…Existing research suggests that peer discrimination for Asian American youth can be attributed to factors that include stereotypes as model minority students, immigrant status, language differences, and smaller physical size (Niwa, Way, Qin, & Okazaki, 2011; Qin et al, 2008). For example, the typecasting of Asian American students as model minorities who are favored by teachers may generate resentment and animosity from non-Asian peers (Rosenbloom & Way, 2004).…”
Section: Discrimination Among Adolescentsmentioning
confidence: 99%
“…Studies have increasingly highlighted Asian American adolescents’ experiences with discrimination, noting their vulnerability to negative treatment from peers in relation to socioemotional and academic outcomes (Benner & Kim, 2009; Qin, Way, & Mukherjee, 2008; Rivas-Drake, Hughes, & Way, 2008). However, a substantial proportion of this research has focused on youth from East Asian backgrounds (Benner & Kim, 2009; Rivas-Drake et al, 2008).…”
mentioning
confidence: 99%
“…The pressure from the model minority label is clear on many Asian immigrants, particularly Southeast Asians, who have failed to meet this expectation (Le, 2011b). Other studies (Qin et al, 2008) have shown that Asian children, because of their association with the model minority myth, have been resented and harassed by students of other races. According to Yu (2006) the high expectations of their peers, teachers, and parents contribute to their higher rate of mental illness.…”
Section: Denied Truth Of Diversitymentioning
confidence: 99%